Bisphenol AF negatively affects oocyte maturation of mouse in vitro through increasing oxidative stress and DNA damage. (25th December 2017) - Ding, Zhi-Ming; Jiao, Xiao-Fei; Wu, Di; Zhang, Jia-Yu; Chen, Fan; Wang, Yong-Sheng; Huang, Chun-Jie; Zhang, Shou-Xin; Li, Xiang; Huo, Li-Jun
Abstract: Bisphenol AF (BPAF) is commonly used in industry production as a substitute for Bisphenol A (BPA). Many studies showed that BPAF negatively affect some physiological processes in humans and animals. However, the effects of BPAF on oocyte maturation and its possible mechanisms are sparsely understood. In the present study, we found that 100 μM BPAF exposure affect oocyte maturation with a decreased first polar body extrusion (PBE) rate. Immunofluorescence study displayed that BPAF exposure disrupt the spindle morphology through affecting the function of microtubule organizing centers (MTOCs), which was confirmed by the dysfunction of γ-tubulin and phosphorylated mitogen-activated protein kinase (p-MAPK). As shown by reactive oxygen species (ROS) accumulation, BPAF exposure also induced oxidative stress. Moreover, DNA damage was significantly increased after BPAF exposure, which may be caused by oxidative stress. In addition, histone modification statuses were changed after BPAF exposure, as shown by western blot with decreased expression of H3K9me3 and H3K27ac. Collectively, our current work demonstrated the possibility of BPAF to negatively impact female fertility and revealed the mechanisms that BPAF disrupted mouse oocyte maturation by affecting cytoskeletal dynamics, inducing oxidative stress, increasing DNA damage, and changing the status of epigenetic modifications. This finding can help develop the potential therapies to alleviate oxidative damage to preserve fertility in people who are often exposed to BPAF environment. Highlights: BPAF exposure affected mouse oocytes maturation. BPAF exposure caused defective spindle morphogenesis and abnormal chromosome alignment in mouse oocytes. BPAF exposure induced oxidative stress in mouse oocytes. BPAF exposure increased DNA damage in mouse oocytes. BPAF exposure affected histone modification in mouse oocytes.